2018
DOI: 10.1021/acs.macromol.7b02619
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amphiphilic Helix–Coil–Helix Poly(3-(glycerylthio)propyl isocyanate)-block-polystyrene-block-poly(3-(glycerylthio)propyl isocyanate)

Abstract: To achieve molecular packing of protic-functionalized helical polymers in aqueous solution, we synthesized an amphiphilic helix–coil–helix triblock copolymer (triBCP) composed of polystyrene and dihydroxyl-functionalized polyisocyanates. Poly­(3-(glycerylthio)­propyl isocyanate)-block-polystyrene-block-poly­(3-(glycerylthio)­propyl isocyanate), P3GPIC-b-PSt-b-P3GPIC, was synthesized by postpolymerization modification. The bidirectional anionic block copolymerization of styrene (St) and allyl isocyanate (AIC) y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The common synthetic methods for polyisocyanates are the anionic polymerization and organotitanium­(IV)-catalyzed coordination polymerization of isocyanates. We consider that the former is better suited in controlling the monomer sequence of copolymer by the choice of comonomers. The kinetics of propagation reaction depends greatly on the structural factors of monomer, such as steric hindrance and electron-donating/withdrawing effect of substituent. The propagating ion pairs of polyisocyanates (amidate ion pairs) are tolerant to a wide variety of functional groups except protic groups due to their weak nucleophilicity. , This factor allows the anionic polymerization of many types of functional isocyanates. …”
Section: Introductionmentioning
confidence: 99%
“…The common synthetic methods for polyisocyanates are the anionic polymerization and organotitanium­(IV)-catalyzed coordination polymerization of isocyanates. We consider that the former is better suited in controlling the monomer sequence of copolymer by the choice of comonomers. The kinetics of propagation reaction depends greatly on the structural factors of monomer, such as steric hindrance and electron-donating/withdrawing effect of substituent. The propagating ion pairs of polyisocyanates (amidate ion pairs) are tolerant to a wide variety of functional groups except protic groups due to their weak nucleophilicity. , This factor allows the anionic polymerization of many types of functional isocyanates. …”
Section: Introductionmentioning
confidence: 99%
“…The sodium ion trapped in the crown ether allowed rapid dissociation of the ion pair (anion of polymer chain end and sodium cation) and led to fast propagation as well as suppression of backbiting due to the extended chain conformation caused by the bulky cation complex associating with the amidate. The living character of the polymerization was confirmed by preparing block copolymers with octyl isocyanate. , An alternative approach to the controlled anionic polymerization of isocyanates by steric hindrance is addition of sodium tetraphenylborate (NaBPh 4 ), which contains a non-nucleophilic anion. This additive interacts with the amidate ion (as initiated by sodium naphthalenide), thereby limiting dissociation of the ion pair in polar solvents. Although the polymerization rate and polymer yield were slightly lower (89% in 10 min), the stability of the ion pair formed between NaBPh 4 and the propagating amidate ions prevented irreversible termination .…”
mentioning
confidence: 99%
“…FIC, AIC, and HIC have conjugated diene, monoene, and alkyl substituents, respectively, at their β-carbons. HIC is the most widely used n -alkyl isocyanate monomer in anionic polymerization. ,, FIC and AIC are often used to prepare side-chain-functionalized polyisocyanates, as the diene and monoene groups of these monomers are available in the post-polymerization modification. ,, The combination of FIC, AIC, and HIC generates three kinds of binary mixtures, FIC:HIC, AIC:HIC, and FIC:AIC.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is believed that each of random, blocky, tapered blocky, gradient, and alternating monomer sequence distributions augment the function of the specific side groups in a distinct cooperative manner. Since the early synthetic contribution by Shashoua, , the precise synthesis of the polyisocyanate copolymers has been feasible by living coordination polymerization of the isocyanates catalyzed by organotitanium­(IV) compounds or living anionic polymerization of the isocyanates initiated by organosodium compounds. We have demonstrated that the anionic copolymerization is useful to achieve distinct monomer sequence distributions depending on the combination of monomers. , …”
Section: Introductionmentioning
confidence: 99%